Promoting Critical Literacy in Enhancing Students' Comprehension of Narrative Texts - Lekawael, Rosina F J (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2020)
Literacy has always become the hottest topic in education field. Critical literacy is a stance, mental posture, or emotional and intellectual attitude that readers, listeners, and viewers bring to bear as they interact with texts. The strength of teaching and learning a language such as English is to develop critical literacy in this case to enhance students’ comprehension of narrative texts. Narrative text is writing in which a story is told, the details may be fictional or based on fact. There are many ways that students demonstrate their understanding of narrative text. There are two diagnostic strategies used to enhance students’ comprehension of a text. The first is anticipation guide, and the second is My turn/Your turn. Anticipation guide is an effective way to activate students’ ideas and information about a topic. Before reading a selection, hearing a presentation, or viewing a film, students respond to several statements that will support or challenge their prior knowledge about the subject. The point is that they can understand and give response to each statement. The anticipation guide strategy can motivate students to give opinion and to discuss in small group. The teacher can assess students’ attitude along the learning activity. She/he also measured students’ reading ability to understand the text given. While, My turn/Your turn is a strategy of pushing students to explore their ideas and perceptions on the article or the text given to them. Through this activity, they conversed to each other and gave opinion, and also finished their worksheet. Implication of this study impacts on English teachers’ role especially in reading skills to be implemented effectively and efficiently to engage students’ comprehension by proposing diagnostic materials.